2004
DOI: 10.1016/s0014-5793(04)00118-8
|View full text |Cite
|
Sign up to set email alerts
|

Rev‐erbα upregulates NF‐κB‐responsive genes in vascular smooth muscle cells

Abstract: Rev-erbK K and retinoic acid receptor-related orphan receptor-K K (RORK K) are orphan nuclear receptors but their effects on transcription are opposed. Here, we show that Rev-erbK K was expressed predominantly in vascular smooth muscle cells (VSMCs) rather than endothelial cells. Overexpression of Rev-erbK K upregulated the expression of interleukin-6 and cyclooxygenase-2, and increased transactivation by NF-U UB and translocation of p65 to the nucleus in A7r5 VSMCs. Furthermore, the expression of Rev-erbK K w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 39 publications
3
49
0
Order By: Relevance
“…overexpression contributes to induction of certain pro-inflammatory genes such as IL6 and COX-2 through NF-B pathway by increasing p65 nuclear translocation (8). Similar findings have also been mentioned in astrocytes, where Rev-erb␣ competes with ROR␣ for the up-regulation of IL6 in NF-B-dependent pathway (35).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…overexpression contributes to induction of certain pro-inflammatory genes such as IL6 and COX-2 through NF-B pathway by increasing p65 nuclear translocation (8). Similar findings have also been mentioned in astrocytes, where Rev-erb␣ competes with ROR␣ for the up-regulation of IL6 in NF-B-dependent pathway (35).…”
Section: Discussionsupporting
confidence: 68%
“…It is encoded on the opposite strand of the thyroid receptor ␣ (c-erbA␣) gene (6). Rev-erb␣ modulates proinflammatory cytokines through 8) and in that regard is similar to heme, its physiological ligand (5). Rev-erb␣ is structurally unusual in that it lacks the C-terminal tail (helix 12) of the ligand binding domain, which is required for co-activator recognition, hence functions as a transcriptional repressor (9).…”
mentioning
confidence: 99%
“…The molecular basis of this modulation involves the direct induction of IB␣ transcription, thereby inhibiting the NFB signaling cascade. Conversely, Rev-erb␣ induces the NFB-mediated activation of the inflammatory cascade, for example, Cox-2 (44). Our studies show that attenuation of Rev-erb␤-mediated gene regulation leads to elevated ROR␣ and IB␣ expression in skeletal muscle cells.…”
Section: Figmentioning
confidence: 58%
“…Recent studies (22,44,45) have demonstrated a role of ROR␣ in the inflammation process. For example, ROR␣ has an anti- inflammatory role by inhibiting tumor necrosis factor-␣-induced gene expression (22).…”
Section: Figmentioning
confidence: 99%
“…Under this point of view, it is also interesting that PBP was found to interact with the estrogen receptor alpha (ERa), serving as a co-activator in the ER signaling and therefore suspected to be involved in breast cell tumorigenicity (13). In addition, there has also been shown that there is a regulatory link between NR1D1 and the NFKB pathway (14).…”
Section: Bodymentioning
confidence: 99%